(3MGTjI Ydi TQM GddeYIs - (3LeGd GdOjf eMeO GdNhfSGQjs
(3ChdgG (B:s
(3HSe Gddg (B.. (3cJGH GdNeS ef CehGd Cgd GdMQH ajNQL Hg eG de jcf dge cCf jchf eZUhHG ZUHG ef eSde Ch eYGgO hCeGfI CeGfI ef GMOgeG hCehGdge jTed eG MhGg GdYScQ heG Mhdg heGde jMhg HNdGa eGd GdHZGI (B...s
(3BNQgG (B:s
.. (3hGdeYfi CUhe TgQG cGFfG bHd TgQ cGf HYOg hcGf TgQ QeVGf bHdg Ch jchf GdTgQ GdKGfj ehUhaG HCfg HYOg hHCf TgQ QeVGf cGf bHdg (B.. (3eeG fbdfG aj JhLjg TgQ QLH , aJCqed , GfJgi (B.s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B( (3ZjQ eDQN (B) : (3eMeO Ydj Hf YHGS GdHdGZj , h (B: (3gGOj Hf YHGS Bd cGTa GdZWGA , SfI (B: 9 (3QHjY GdKGfj (B1314 (3g`s
Keywords: (3abg GdePGgH GdCNQis